IMPROVING THE TENTH GRADE STUDENTS’ SPEAKING ABILITY OF SENIOR HIGH SCHOOL HARAPAN-I MEDAN THROUGH ROLE PLAY METHOD - Firdayanti Firdaus; Dwi Suci Amaniarsih (Journal MELT (Medium for English Language Teaching), 2019)
The purpose of this study was to find out how the application of role plays methods in an effort to improve English speaking skill of the tenth grade students at SMA Harapan-I Medan. This research is a Classroom Action Research study conducted collaboratively. Subjects in this study were students of the tenth grade students at SMA Harapan-I Medan. While the object of this study is the application of role play methods, to improve students' speaking skill. Based on the results of the study, it was found that the percentage of the results of the completeness of the students' scores between cycle I and cycle II had increased. In the first cycle, the percentage of completeness was 40% while in the second cycle there was a significant increase to 63%. There is a 43% increase between the pre-cycle, actions of cycle I and cycle II. Thus this study was declared successful and it can be said that the use of role play methods can improve student learning outcomes in speaking